2022
DOI: 10.1111/hel.12883
|View full text |Cite
|
Sign up to set email alerts
|

“True” Helicobacter pylori infection and non‐cardia gastric cancer: A pooled analysis within the Stomach Cancer Pooling (StoP) Project

Abstract: Background Helicobacter pylori is the most important risk factor for non‐cardia gastric cancer (NCGC); however, the magnitude of the association varies across epidemiological studies. This study aimed to quantify the association between H. pylori infection and NCGC, using different criteria to define infection status. Methods A pooled analysis of individual‐level H. pylori serology data from eight international studies (1325 NCGC and 3121 controls) from the Stomach Cancer Pooling (StoP) Consortium was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
(153 reference statements)
1
7
0
Order By: Relevance
“…Previous studies have consistently illustrated a strong association between H. pylori and NCGC worldwide, although the magnitude of the association varied between studies 6,7,23 . Our results showed a more than fourfold higher risk of NCGC in infected individuals in both East Asia and West.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous studies have consistently illustrated a strong association between H. pylori and NCGC worldwide, although the magnitude of the association varied between studies 6,7,23 . Our results showed a more than fourfold higher risk of NCGC in infected individuals in both East Asia and West.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have consistently demonstrated a significant association between non‐cardia gastric cancer (NCGC) and H. pylori infection; however, the strength of the association varied between studies 6–9 . Furthermore, it remains controversial whether H. pylori infection plays a role in the progression of cardia gastric cancer (CGC), which shows an increasing trend of incidence globally 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive literature-based evidence suggests that there is no difference in H. pylori seroprevalence between individuals with intestinal or diffuse tumors. [29][30][31] Notably, long-term prospective studies show that H. pylori infection increases the risk of both Laurén types. 27,32 In agreement, the ABC screening method (based on combined results of H. pylori serology and pepsinogen levels) is useful for the detection of both intestinal and diffuse types.…”
Section: A Sso Ciati On With H Pylori Infec Ti On and Cofac Tor Smentioning
confidence: 99%
“…19,29 H. pylori is a more potent risk factor for non-cardia gastric cancer compared with cardia tumors. 30 Similar to the risk of GIM, CagA gene status plays an important role in the progression to gastric cancer, with a 2.87-fold (95% CI, 1.71-3.05) increase in gastric cancer risk among those infected with a CagA-positive strain of H. pylori. 31 The decline in the incidence of gastric cancer has largely mirrored the decline in H. pylori prevalence.…”
Section: H Pylori Infectionmentioning
confidence: 99%